Analisis Usability Web E-Learning STKIP Bangkalan sebagai Media Pembelajaran Daring dengan Metode Usability Testing - Viola Budi Antika; Prita Dellia; Diana Syifah; Dewi Kusuma Wardani; Muhammad Alfis Sholikhin (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This study analyzes the usability of the STKIP Bangkalan e-learning website as an online learning medium using the System Usability Scale (SUS) method. The evaluation covers five aspects of usability, namely learnability, efficiency, memorability, errors, and satisfaction, through a questionnaire filled out by students. The title "Analysis of the Usability of the STKIP Bangkalan E-Learning Website as an Online Learning Medium with the System Usability Scale Method" was chosen because it reflects the main focus of the study, the object studied, and the evaluation method used. The selection of this title also aims to make it easy for readers to understand the scope, context, and methodological approach applied in this study. The results of the study indicate that the STKIP Bangkalan e-learning website has a fairly good level of usability, with a System Usability Scale (SUS) value of 64.98. Based on the standard interpretation of SUS, this score is included in the "fairly acceptable" category (marginal acceptability), which indicates that the e-learning web application has fulfilled its basic function as an online learning medium, although improvements are still needed in the navigation and interface aspects to improve the overall user experience.